Outcomes of patients with acute kidney injury with regard to time of initiation and modality of renal replacement therapy – first data from the Silesian Registry of Intensive Care Units - Czempik, Piotr; Cieśla, Daniel; Knapik, Piotr; Krzych, Łukasz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Introduction : Acute kidney injury (AKI) remains a serious clinical problem in the intensive care unit (ICU). It constitutes an independent risk factor for mortality, especially when renal replacement therapy (RRT) is required. Aim : Due to limited evidence pertaining to timing, choice of RRT modality and lack of studies investigating AKI in Polish ICUs, we sought to analyse outcomes of adult AKI-RRT ICU patients in the Silesian Voivodeship. Material and methods: We analysed data regarding 1,380 patients with AKI who required RRT (AKI-RRT) (9.2% of all subjects in the registry) hospitalized between October 2011 and December 2014 in Silesian ICUs. The primary outcome was crude ICU mortality. Length of ICU stay (LOS) was considered the secondary outcome. Results : Of 15,030 patients 1,380 (9.2%) individuals developed AKI requiring RRT. The overall mortality in the registry was 43.9%, but it was significantly higher (69.1%) in AKI-RRT patients (p < 0.01). Mortality with regard to timing of institution of RRT was 67.1% in the group with RRT instituted prior to ICU admission (RRT-prior-ICU) and 69.4% in patients with RRT instituted during ICU hospitalization (RRT-in-ICU) (p = 0.58). Conclusions : Multiple patient- and hospitalization-related factors determine mortality in this specific cohort. There are no differences in mortality with regard to RRT being initiated before or during hospitalization in the ICU. Due to multiple confounders, differences in mortality in terms of modality of RRT should be interpreted with caution.